Rationality and ethical sensitivity in nursing care for patients admitted to a Peruvian public hospital of Level II-2 - Linares-Olano, Ingrid Asucena (2022)
Background: In nursing, the ethical experience connotes being always affective-reflexive, when exercised in contexts of fragility and vulnerability of patients, requiring care and health professionals to act with such criteria, benefiting the people cared for. Objective: To describe the rationality and ethical sensitivity in nursing care for patients in a level II-2 Peruvian public hospital. Material and methods: The qualitative, descriptive approach was assumed under hermeneutic analysis design. The sample consisted of 15 nurses, obtained through non-probabilistic convenience sampling, who worked in the Internal Medicine area of ​​the aforementioned public hospital. Information was collected through a semi-structured interview applied by digital means, with prior informed consent. The data was processed through content analysis. Results: a) Availability and effort towards compassionate and supportive care, b) Balancing duties and affections towards the global good of the patient, c) Interactive understanding, trust and good treatment until the end of life. Conclusion: The results highlight the nurse's ability to apply affectivity, empathy, affective communication, attentive gaze and physical contact; as well as the availability to listen and interpret the needs, in addition to understanding the anguish, suffering, fears and pain of the person when they are admitted to a hospital.